Contrast of Laryngeal Mask Airway Versus Endotracheal Tube for Early Postoperative Recovery Following Laparoscopic Cholecystectomy - Aqil Qayoom, Ahmed Uddin Soomro, Kelash Kumar, Imran Ali, Maqsood Ahmed Siddiqui, Imran Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the difference between laryngeal mask airway versus endotracheal tube for early postoperative recovery following laparoscopic cholecystectomy Study design: A randomized controlled trial Place and Duration: This study was conducted in Liaquat National Hospital and Medical College Karachi from June 2020 to June 2021 Methodology: Overall, 60 individuals were assigned to airway management utilizing either the laryngeal mask airway(LMA) group or endotracheal tube (ETT) group. All the patients went under sevoflurane-based general anesthesia and all of them had a laparoscopic cholecystectomy. Three things were recorded before and after carbo peritoneum that was blood pressure, heart rate and peak airway pressure. The first hour after surgery and the first postoperative day were used to assess postoperative pain and analgesic needs, as well as hoarseness, nausea, sore throat, and dysphonia. Results: Two attempts were made to have a successful Laryngeal mask airway or endotracheal tube placement. During carbo peritoneum, both of the groups, LMA and ETT had similar highest average peak airway pressure (LMA: 17.8 [2.9], ETT: 18.2 [4.1], with a p-value of 0.159). The incidence of bradycardia and elevated systolic blood pressure was higher in the LMA group. The LMA group had lower pain scores one hour postoperatively and on a postoperative day 1 than the ETT group (LMA: 3.9 [2.0], ETT: 5.4 [2.3], with a p-value of 0.017 and LMA: 5.6 [1.9], ETT: 6.7 [1.7], with a p-value of 0.042). Both the groups had the same analgesic requirements. Until postoperative day 1, the LMA group had a lower incidence of nausea than the ETT group (LMA: 4/28 [14%], ETT: 12/28 [43%], with a p-value of 0.032). Conclusion: The Laryngeal Mask Airway Protector proved to be a successful ventilator device which showed lesser intraoperative hemodynamic stress responses. It also enhanced the early recovery standard following laparoscopic cholecystectomy. Keywords: Endotracheal tube, laparoscopic cholecystectomy, Laryngeal mask airway